Diagnostic challenge: an atypical presentation of infective endocarditis. Issue 1 (25th January 2021) - Parente, Cristina Sarah; Sandland-Taylor, Laura Emma; Akhtar, Waheed
Abstract : It is recognised that infective endocarditis is frequently a challenging diagnosis to make, as it may present with a range of non-specific symptoms. A middle-aged man was admitted with an 8-day history of profuse non-bloody diarrhoea and vomiting. He had no medical history and no identifiable risk factors for infective endocarditis, and so this in combination with the patient's atypical symptoms presented a diagnostic challenge. The patient was eventually diagnosed with a Staphylococcus aureus right-sided infective endocarditis. This case report explores the events which led to this diagnosis and demonstrates a number of unique learning points. It also highlights the importance of maintaining an open mind and being prepared to revise an initial diagnosis in the face of medical uncertainty.